The Implementation of Proof-of-Work Technology in the Security of Job Training by the Surakarta City Manpower Office - Agus Putra, Affriza Brilyan Relo Pambudi (Journal of Artificial Intelligence and Software Engineering, 2025)
This study aims to implement Proof-of-Work (PoW) innovation as a security component in the job training system managed by the Surakarta City Manpower Office. In the rapid development of technology, information security is a very important aspect, especially in the implementation of training activities involving sensitive data from participants and instructors. This study uses a prototyping approach to design, implement and test a PoW blockchain technology-based system to ensure information security in job training. The prototyping approach was chosen because it allows a rapid development process that is immediately applied to perfect the system. This system is designed in such a way that every data entered into the training track record is secured through a mining process, which ensures its integrity and security. The results of PoW technology are able to verify new transactions and data entered so that only valid and encrypted information can be received and stored. In conclusion, the implementation of a PoW-based security system on this job training platform has proven to be successful in increasing data protection and preventing manipulation by irresponsible parties. Thus, PoW technology not only provides a higher level of information security, but also increases the trust of participants and job training organizers at the Surakarta City Manpower Office.